The Relationship Between Top Management Team–Outside Board Conflict and Outside Board Service Involvement in High‐Tech Start‐Ups1. (21st February 2017) - Vandenbroucke, Elien; Knockaert, Mirjam; Ucbasaran, Deniz
Abstract : Corporate governance research has extensively studied the relationship between outside board characteristics and outside board involvement. We add to this literature by investigating the extent to which interactions between outside board members and the top management team (TMT) affect the functioning of the outside board. Building on conflict theory, our study shows that conflict between TMT and outside board is an important antecedent for outside board service involvement. Specifically, drawing from a hand‐collected data set of 70 high‐tech start‐ups in Belgium, we find that TMT–outside board task conflict is both directly and indirectly, that is, through TMT–outside board relationship conflict, related to outside board service involvement.